Utilising the Think-Pair-Share Technique in the Learning of Probability - Lee, Cheryl; Li, Hui-Chuan; Shahrill, Masitah (Universitas Ahmad Dahlan, 2018)
The main objective of this study is to investigate the effects of collaborative learning on studentsâ understanding of probability and their attitudes towards mathematics. The participants were 15 Year 10 students selected by convenience sampling at a secondary school in Brunei Darussalam. In total, six intervention lessons with the application of Think-Pair-Share strategy were conducted. Data collection methods included a series of tests (pre- and post-tests and delayed post-test), surveys, studentsâ interviews and lesson observations. The findings revealed improvements in the studentsâ test scores and they were able to retain their knowledge after a period of time. From the triangulated data, it was found that the students demonstrated an increase in their self-efficacy, participation, understanding and enjoyment levels after the intervention. Their enjoyment towards learning probability was derived from being able to communicate with their peers. The students showed more enthusiasm and participation in class as the lessons progressed.